Costimulation of Murine Osteoblasts with Interferon-γ and Tumor Necrosis Factor-α Induces Apoptosis through Downregulation of Bcl-2 and Release of Cytochrome c from Mitochondria. (9th August 2018) - Iguchi, Mayumi; Hiroi, Miki; Kanegae, Haruhide; Ohmori, Yoshihiro
Abstract : During chronic inflammation from diseases, such as periodontal disease, the proinflammatory cytokines interferon-gamma (IFN γ ) and tumor necrosis factor- α (TNF α ) alter bone remodeling. To elucidate the underlying molecular mechanisms, we investigated the effect of IFN γ and TNF α on the proliferation and survival of clonal MC3T3-E1 mouse osteoblasts. We found that although IFN γ or TNF α alone affected cell growth and survival only marginally, costimulation with both synergistically inhibited cell growth and reduced cell viability. The diminished cell viability was due to apoptosis, as indicated by increased TUNEL staining and elevated caspase 3, 8, and 9 activities. Western blot also showed that costimulation with IFN γ and TNF α elicited cytochrome c release and downregulated B cell lymphoma 2 (Bcl-2) expression without affecting Bcl-2-associated X (Bax) protein expression. Furthermore, stable Bcl-2 overexpression significantly alleviated cell death following costimulation. Collectively, these results suggested that IFN γ and TNF α elicited osteoblast apoptosis via cytochrome c release from damaged mitochondria, caspase activation, and Bcl-2 downregulation.